Sistem Informasi Manajemen Aset Pada PT.XYZ Menggunakan Metode Garis Lurus - Dini Eka Pratiwi; Tacbir Hendro Pudjiantoro (Prosiding SISFOTEK, 2020)
XYZ is engaged in trade and services. The process of recording asset planning data planning and submission is not well recorded in one document, this causes frequent data mismatches, the process of asset maintenance is not recorded properly so that it does not know what assets have been maintained and when making depreciation calculations often experience errors in calculating depreciation costs caused by errors in determining the acquisition cost or errors in estimating the economic life that can cause company profits to be smaller, with the existence of asset management at PT. XYZ can help the problems that exist in the company. The output of this research is expected to produce a system that can help companies in asset data management, asset planning, asset filing, asset maintenance and asset depreciation using the straight line method.